Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Pengelolaan Keuangan pada Member Gym di PT Kiduanam Zamrud Sejahtera (USB Fitness) - Leo Rafi Pratama; Usran Masahere; Asep Asep (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of financial literacy and lifestyle on financial management among gym members at USB Fitness. Financial literacy refers to the ability to understand and apply financial concepts, while lifestyle encompasses spending patterns, consumption preferences, and daily habits. Low financial literacy combined with a high-consumption lifestyle can negatively impact personal financial management, potentially leading to poor budgeting, excessive debt, and limited savings.The research adopts a quantitative approach using a survey method, with data collected through structured questionnaires distributed via Google Forms. The population comprises 60 registered gym members, from which a sample of 52 respondents was determined using the Slovin formula with a margin of error of 5%. Data analysis techniques involve both partial (t-test) and simultaneous (F-test) hypothesis testing to assess the effects of the independent variables—financial literacy and lifestyle—on the dependent variable, financial management.The t-test results indicate that financial literacy has a positive and significant effect on financial management (t-count = 6.384 > t-table = 2.00958; p-value = 0.000 < 0.05), suggesting that higher financial literacy levels contribute to more effective personal financial practices. Conversely, lifestyle shows no significant effect on financial management (t-count = -0.013; p-value = 0.990 > 0.05), indicating that lifestyle variations among respondents do not directly determine their financial management capabilities.Simultaneous testing through the F-test reveals that financial literacy and lifestyle together have a significant influence on financial management (F-count = 21.333 > F-table = 3.191; p-value = 0.000 < 0.05). This suggests that while lifestyle alone may not significantly impact financial management, its interaction with financial literacy can influence financial outcomes.The study concludes that improving financial literacy among gym members is essential for enhancing financial management skills, while lifestyle modifications may only be impactful when supported by strong financial knowledge.